Common respiratory and gastrointestinal illness in paediatric student nurses and medical technology students. - Gerth, H. J. (Cambridge University Press, 1987)
The aim of this study was to establish the risk of acquiring common respiratory and gastrointestinal illness for paediatric nurses. Using self-administered questionnaires, student nurses at two children's hospitals and students at one school of medical technology reported biweekly the number of minor illnesses, symptoms, and indicators of severity of infection over a 3-year period (1975-8). Although a systematic bias was evident with some symptoms, others appeared to be quite reliable. The following four syndromes were defined to estimate the risk: upper respiratory syndrome (URS), lower respiratory syndrome (LRS), respiratory and gastrointestinal syndrome (RGS), and gastrointestinal syndrome (GS). Surveillance days were allocated to groups with high- or low-intensity contact with children. The incidence of all illnesses was 2.9 per person-year in the low-intensity contact group and 4.4 per person-year in the high-intensity contact group. The reported incidence of LRS and RGS in the high-intensity contact group was 1.55 times higher than in the low-intensity group (P less than 0.001). LRS and RGS incidence was similar in nurses at both schools. During low contact periods it corresponded to that of the medical technologists.